If A and B are the roots of the quadratic equation x 2 - 4x + 1 = 0, the value of A 3 + B 3 is
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
how to analyze the quadratic
Log in to reply
For a quadratic equation a x 2 + b x + c = 0 , the sum of the roots is a − b and product of the roots is a c .
it easier than my way.
For a quadratic equation a x 2 + b x + c = 0 , sum of the roots is a − b and product of the roots is a c .
So, here A + B = 4 and A*B = 1.
We need to calculate A 3 + B 3 :
A 3 + B 3 = ( A + B ) ( A 2 + B 2 − A B ) ..... Identity of sum of cubes
= ( A + B ) ( ( A + B ) 2 − 2 A B − A B ) ..... Identity of sum of squares
Substitute the values of A + B and AB,
= (4)( 4 2 − 2 × 1 − 1 )
= 5 2
That's the answer!
NICE SOLUTION SIR ! CAN WE ALSO SOLVE IT BY QUADRATIC FORMULA?
Log in to reply
Or suppose if you solve the same sum by taking the quadratic equation: x 2 + x + 1 = 0 . If you find its roots using the quadratic formula, it would lead into complex results. You would then have to find the cubes of those complex numbers.
This sum and product formulae would help here. I hope you are getting what I am trying to say!
You can solve it using that too. In this case, it would be easy to calculate the roots, in fact. But usually the method I wrote is preferred, as it can be used very easily for big quadratic equations too.
I suggest you remember these formulae. It would come in handy in lots of mathematical problems.
Log in to reply
OK SIR I GOT IT ! THANK YOU !!
From the property of quadratic polynomials, it is clear that A + B = 4 and A B = 1
( A + B ) 3 = A 3 + B 3 + 3 A B ( A + B ) .
Substituting the values and solving the equation for A 3 + B 3 , we get the answer as 5 2 .
We have the equation x 2 − 4 x + 1 = 0 with roots A and B.
We know, A + B = (-(coefficient of x))/(coefficient of x 2 ) = 1 − ( − 4 ) = 4
Also, A B = (constant term of the polynomial)/(coefficient of x 2 ) = 1 1 = 1
Now, A 3 + B 3 = ( A + B ) ( A 2 − A B + B 2 ) = ( A + B ) ( ( A + B ) 2 − 3 A B ) = 4 ( 4 2 − 3 × 1 ) = 4 ( 1 6 − 3 ) = 4 × 1 3 = 5 2
A and B are roots of eqn. x 2 -4x+1=0
So, A+B= 4 / 1
AB=1
A 3 + B 3 = ( A + B ) 3 -3 AB (A+B)
Putting value of A+B and AB we get A 3 + B 3 =52
Since it is a quadratic equation,
The sum of the roots i.e. A+B= -(coefficient of x)/(coefficient of x^2)
Therefore, A+B= -(-4)= 4
The product of the roots i.e. A*B = (constant)/(coefficient of x^2)
Therefore, A*B = 1
Since we need A^3 + B^3 that is equal to (A + B)(A^2 -A*B + B^2), we need to find the value of A^2 + B^2.
We know that, (A + B)^2 = A^2 +2 A*B + B^2
Therefore, A^2 + B^2 = (A + B)^2 - 2 A*B
Putting the values, we get
A^2 + B^2 = (4)^2 - 2*1
= 16 - 2
= 14
Now, A^3 + B^3 = (A + B)(A^2 -A*B + B^2)
= (A + B)(A^2 + B^2 -A*B)
= 4(14 - 1)
= 4*13
= 52
A 3 + B 3 = ( A + B ) 3 − 3 A B ( A + B ) From Vieta's formulas we know that A + B = 4 , A B = 1 .So A 3 + B 3 = 4 3 − 3 ( 1 ) ( 4 ) = 6 4 − 1 2 = 5 2
according to the quadratic equation x=(-b±√(b^2-4ac))/2a. x = 2+3^1/2 (A) and 2-3^1/2 (B) . let them be equal to A and B. then solving by the identities (a+b)^3 = a^3 + b^3 + 3ab(a+b) and (a-b)^3 = a^3 - b^3 - 3ab(a-b) ,, we gt A^3 + B^3 = 52
If A and B are the roots of the given equation then A + B = 4 and A B =1 Then A^{3} + B^{3} = (A + B )^{3} - 3AB(A + B) = 4^{3} - 3 1*4 = 64 -12 = 52
IF P & Q ARE ROOTS OF A QUADRATIC EXPRESSION ax^2+bx+c=0 THEN P+Q=-b/a AND P*Q=c/a A+B= -b/a = - (- 4)/1 = 4 and AB = c/a = 1/1 = 1 hence, A^3 + b^3= (A+B)^3 - 3 AB (A+B) => 4^3 - 3 (1) (4) => 64 - 12 => 52
let A+B = -b/a and AB = c/a. and A^3 + b^3 = (A+B)^3 -3AB(A+B) so (4)^3 -3(1)(4) = 52
alpha + beta are the roots of quadratic equation ( class 9 th syllabus )
alpha + beta = -b/a = 4 alpha * beta = c/a = 1 (alpha + beta )^3 = alpha^3 + beta^3 + 3 alphta * beta ( alpha + beta ) [[a+b)^3 = a^3 + b^3 + 3ab(a+b)]]
=4^3 + 3 (1) (-4) = 64 -12
We know that if A and B are the roots of a quadratic ax^{2} + bx + c then, A+B= \frac{-b}{a} & AB= \frac{c}{a} . So, A+B=4 and AB=1. And we know that (A+B)^{3} = A^{3} + B^{3} + 3AB(A+B) or A^{3} + B^{3} = (A+B)^{3} - 3AB(A+B). Substituting the values of (A+B) and (AB) in the equation, A^{3} + B^{3} = 4^{3} - 3(1)(4) = 64-12 = \boxed{52}
A and B are the roots of the quadratic equation x2 - 4x + 1 = 0 <=> A + B = 4, A x B = 1. A^3 + B^3 = (A + B)(A^2 - A x B + B^2) = (A + B)[(A + B)^2 - 3x A x B] = 4 x ( 4^2 - 3 x 1) = 52
A+B= 4 AB=1 since, (A+B)^3= A^3 +B^3 + 3AB(A+B) this implies, A^3 + B^3 = (A+B)^3- 3AB(A+B) or A^3 + B^3 = 4^3 -3(4) or A^3 + B^3 = 52
Sum of the roots A+B =-b/a = 4 and Product of the roots AB =c/a = 1
Then we use A^3 +B^3 = (A+B)^3 -2AB(A+B) = (4)^3 -3 1 4 = 52
The formula is A^3 +B^3 = (A+B)^3 -3 AB(A+B) = 4^3 -3 1*2 = 52.There was a typo earlier.I am sorry
from given equation,we get A+B=4 and AB=1 ( as given roots are A and B ) ,So we get A^3+B^3= 4^3-3 1 4=52
If A and B are the roots of the equation x 2 − 4 x + 1 = 0 then the equation can be written as ( x − A ) ( x − B ) = 0 ⟺ x 2 − ( A + B ) x + A B = 0 . Therefore A + B = 4 .
That A 2 − 4 A + 1 = 0 and B 2 − 4 B + 1 = 0 is true since A and B are the roots of the equation. By addition, ( A 2 + B 2 ) − 4 ( A + B ) + 2 = 0 , so A 2 + B 2 = 4 ( A + B ) − 2 = 1 4 .
Also A 3 − 4 A 2 + A = 0 and B 3 − 4 B 2 + B = 0 , by addition again, ( A 3 + B 3 ) − 4 ( A 2 + B 2 ) + ( A + B ) = 0 , so A 3 + B 3 = 4 ( A 2 + B 2 ) − ( A + B ) = 5 2 .
Problem Loading...
Note Loading...
Set Loading...
Analyzing the quadratic, we can see that A + B = 4 and A B = 1 .
Since A 2 + B 2 = ( A + B ) 2 − 2 A B and A 3 + B 3 = ( A 2 − A B + B 2 ) ( A + B ) , we can simply plug the values to find out that A 2 + B 2 = 4 2 − 2 = 1 4 and thus A 3 + B 3 = ( 1 4 − 1 ) × 4 = 5 2 .